Antithrombin‐III mitigates thrombin‐mediated endothelial cell contraction and sickle red blood cell adhesion in microscale flow. (13th July 2022) - Wulftange, William J.; Kucukal, Erdem; Man, Yuncheng; An, Ran; Monchamp, Karamoja; Sevrain, Charlotte D.; Dashora, Himanshu R.; Owusu‐Ansah, Amma T.; Bode, Allison; Ilich, Anton; Little, Jane A.; Key, Nigel S.; et al.
Summary: Individuals with sickle cell disease (SCD) have persistently elevated thrombin generation that results in a state of systemic hypercoagulability. Antithrombin‐III (ATIII), an endogenous serine protease inhibitor, inhibits several enzymes in the coagulation cascade, including thrombin. Here, we utilize a biomimetic microfluidic device to model the morphology and adhesive properties of endothelial cells (ECs) activated by thrombin and examine the efficacy of ATIII in mitigating the adhesion of SCD patient‐derived red blood cells (RBCs) and EC retraction. Microfluidic devices were fabricated, seeded with ECs, and incubated under physiological shear stress. Cells were then activated with thrombin with or without an ATIII pretreatment. Blood samples from subjects with normal haemoglobin (HbAA) and subjects with homozygous SCD (HbSS) were used to examine RBC adhesion to ECs. Endothelial cell surface adhesion molecule expression and confluency in response to thrombin and ATIII treatments were also evaluated. We found that ATIII pretreatment of ECs reduced HbSS RBC adhesion to thrombin‐activated endothelium. Furthermore, ATIII mitigated cellular contraction and reduced surface expression of von Willebrand factor and vascular cell adhesion molecule‐1 (VCAM‐1) mediated by thrombin. Our findings suggest that, by attenuating thrombin‐mediated EC damage and RBC adhesion to endothelium, ATIII may alleviate the thromboinflammatory manifestations of SCD.